Carboxymethyl Cellulose (CMC) based Green Synthesis of Metal and Metal Oxide Nanoparticles and its Applications: Mini-Review - Ahmad, Waseem; Singh, Ajay; Manral, Meghna; Pandey, Shivam; Rashid, Mohd. (Asian Journal of Chemistry, 2023)
Due to its distinct and unique surface morphology, mechanical strength, tunable solubility in water, viscous properties, ease of access and enormous amount of raw materials, low-cost synthesis process and similarly several more opposing characteristics, carboxymethyl cellulose (CMC) based materials have wide applications. While synthesizing nanoparticles, CMC appears to be better as both a reducing and stabilizing agent. CMC would have no detrimental effects on human health or the environment and also is non-toxic and biodegradable. Hence, CMC mediated metal and metal oxide nanoparticles have multiple benefits in the areas of antibacterial, antimicrobial, antidiabetic, anti-inflammatory, wound healing, antioxidant, as well as optical properties. In this mini-review article, the role of carboxymethyl cellulose (CMC) is highligted in the fabrication of nanoparticles.